Channelising People's Power towards Protection and Management of Protected Areas - Jha, Mohan (Indian Forester, 2000)
This paper deals with a case study of newly constituted 'Gyanganga' Sanctuary in Buldhana District of Maharashtra. Local communities around the forests in the Ajanta hills organised themselves and removed the 'Kathiawadis' along with their 40,000 cattle and also controlled the illegal sheep grazing in the forests. They also controlled the illicit felling and fire and catalysed the natural regeneration without any financial support. Local communities could get some benefits from the sale of Anjan leaves and grass, which in turn could lead to stall-feeding. Efforts of the local communities culminated in the formation of new 'Gyanganga' Wildlife Sanctuary.